Money : myths, truths and alternatives - Mellor, Mary (Chicago, IL : Policy Press, 2019)
Mary Mellor examines money's social, political and commercial histories to debunk longstanding myths such as money being in short supply and needing to come from somewhere. She sets out a new finance system, based on green and feminist concerns, to bring radical change for social good.
Front Cover; Title Page; Copyright; Contents; About the Author; Acknowledgements; Introduction: unlocking the mysteries of money; One: A fairy tale about money: myths and their consequences; Two: Old magic: money before states and markets; Three: The king was in his counting house: money and the state; Four: Conjuring money out of thin air: money and banking; Five: The sorcerer's apprentice: magic money out of control; Six: Ditching the sorcerer: money without the state; Seven: Breaking the spell: money for the people; Notes; References; Annotated bibliography; Index
Online resource; title from PDF title page (EBSCO, viewed June 28, 2019)
JSTOR
Keywords: Money; Finance, Public; Social justice; Social Justice; Finances publiques; Justice sociale; LAW -- Jurisprudence; Finance, Public; Money; Geldpolitik; Geld